1990
DOI: 10.1128/jcm.28.9.2012-2016.1990
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic study of Taylorella equigenitalis strains by field inversion gel electrophoresis of genomic restriction endonuclease fragments

Abstract: Contagious equine metritis (CEM), a sexually transmitted bacterial disease, was first described in thoroughbred horses. It also occurs in nonthoroughbred horses, in which it produces isolated, apparently unrelated outbreaks. Thirty-two strains of Taylorella equigenitalis, the causative agent of CEM, from all over the world were characterized by field inversion gel electrophoresis of fragments of genomic DNA obtained by digestion with low-cleavage-frequency restriction enzymes. This resulted in a division into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 12 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…This may not be necessary since we know that there are different genomic lines among T. equigenitalis isolates (2) and that a PCR based on 16S rDNA sequences does not discriminate between these lines. Since the symptoms of infection differ between animals, it may be possible that T eqluigeniitalis isolates differ in their virulences.…”
Section: Resultsmentioning
confidence: 99%
“…This may not be necessary since we know that there are different genomic lines among T. equigenitalis isolates (2) and that a PCR based on 16S rDNA sequences does not discriminate between these lines. Since the symptoms of infection differ between animals, it may be possible that T eqluigeniitalis isolates differ in their virulences.…”
Section: Resultsmentioning
confidence: 99%
“…CEM was first reported in 1977 in the United Kingdom and Ireland among Thoroughbred horses (Crowhurst, 1977;Timoney et al, 1977), but is currently a worldwide concern in various equine breeds (Jeoung et al, 2016;Schulman et al, 2013) with the hypothesis that the episodic "source of contagion" is often mainland Europe (Schulman et al, 2013). Pulsedfield gel electrophoresis (Aalsburg and Erdman, 2011;Sting et al, 2016) and several other molecular typing tools including field inversion gel electrophoresis (Bleumink-Pluym et al, 1990), chromosomal DNA fingerprinting (Thoresen et al, 1995), crossed-field gel electrophoresis (Miyazawa et al, 1995) and more recently repetitive extragenic palindromic PCR (Sting et al, 2016) have been used to genotype CEM isolates. However, these molecular epidemiological tools are not very portable and inter-laboratory results are difficult to compare (Maiden et al, 1998), making them ill-suited for global epidemiological studies of 5 CEM outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study (1), we demonstrated that T. equigenitalis strains can be divided into groups by genomic DNA digestion with the restriction enzyme ApaI in conjunction with field inversion gel electrophoresis (FIGE). A total of 32 T. equigenitalis strains were characterized, and some strains showed similar patterns, which correlated with epidemiological data.…”
mentioning
confidence: 99%